THE APPLICATION OF THE EXACT INTEGRAL TO THE PROBLEMS OF MECHANICS (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This article explores the significant role of exact integrals in solving complex mechanics problems. It delves into the methods of utilizing exact integrals, their applications in mechanics, and the impact of these techniques on obtaining accurate results. The article highlights the importance of these mathematical tools in tackling intricate mechanical scenarios and provides insights into the broader implications of their implementation.